The natural law as a legitimating filter of aragonese freedoms in the constitutive process of the spanish national state - Vicente y Guerrero, Guillermo (Revista de derecho aragonés, 2021)
The Aragonese humanist Braulio Foz participated through some writings in the transcendental debate that discussed the construction of the Spanish national state, requesting the implementation for the national community of some of the old Aragonese fueros, freedoms and institutions. For that, Foz will argue its superiority to law and institutions both Castilian and the rest of ancient kingdoms, for its determined commitment to freedom and their no contradiction with the principles of natural law. To support his position, he elaborated his own legal philosophical system, in wich the will, whose major purpose is to satisfacy a whole series of natural needs that make up the true essence of the natural law, was the main feature of the human being.
Keywords: Natural law; Aragonese freedoms; Spanish national state; 19th century; Braulio Foz